High serum interleukin-18 concentrations in patients with coronary artery disease and type 2 diabetes mellitus. - Suchanek, H; Myśliwska, J; Siebert, J; Wieckiewicz, J; Hak, Ł; Szyndler, K; Kartanowicz, D (2005)
AIMS: The aim of our study was to analyse the serum level of interleukin 18 (IL-18) in coronary artery disease (CAD) patients with type 2 diabetes mellitus (DM), and to relate this to clinical findings. METHODS: The IL-18 level was measured by ELISA in serum samples from 130 CAD patients prior to their first, elective, coronary artery bypass surgery. Forty-three of them had been diabetic for several years. A control group consisted of 31 healthy people matched according to age, BMI, lipid and smoking status. RESULTS: The CAD patients with DM were similar to the non-diabetic CAD patients with respect to age, BMI, grade of heart failure, ejection fraction. There were no differences in the duration of CAD, history of myocardial infarction and PTCA or instability of angina. The serum level of IL-18 was higher in the CAD patients than in the control group. The CAD patients with DM had a higher concentration of IL-18 compared to the non-diabetic CAD group. The diabetic patients with triple-vessel disease were characterized by a higher concentration of IL-18 than the non-diabetic patients with the same grade of CAD. Smoking affected the IL-18 concentration, particularly in the diabetic patients. CONCLUSION: Type 2 DM predisposes patients, especially those with multi-vessel CAD who were smokers, to a higher serum level of IL-18, which may help explain their vulnerability to fatal, secondary cardiovascular events. These patients should be in the first line for stringent, secondary cardiovascular prevention.